Comparison of outcomes of stereotactic body radiation therapy delivered with three different technologies to the lung - Kumar, Sameera S. (J Radiosurg SBRT, 2018)
PURPOSE/OBJECTIVE(S): Since the inception of stereotactic body radiation therapy (SBRT), treatment delivery has been performed with volumetric modulated arc therapy (VMAT), helical tomotherapy (HT) and noncoplanar static fields (SF). The purpose of this study is to compare SBRT delivery among these treatment modalities to the lung. MATERIALS/METHODS: A retrospective review of SBRT treatments of 30 to 60 Gy in 1 to 5 fractions from 2007 to 2015 was performed. Dosimetric parameters included V5, V20, D2cm, gross tumor volume (GTV) and planning target volume (PTV) size and coverage, rib/esophageal minimum/maximum doses, R30Gy, R50%, and the conformality index (CI). Clinical outcomes evaluated included local control, pneumonitis and other toxicities. ANOVA, Student’s t-test and Kruskal-Wallis test were used to compare the parameters among modalities. Kaplan-Meier estimates of time-to-local failure were produced. RESULTS: 176 Treatments included 106 SF, 36 VMAT and 34 HT. HT had better PTV coverage (p=0.0166) but higher lung V5 and esophageal doses (p<0.001 and p=0.0032). R30Gy, R50%, and CI were significantly better with VMAT SBRT (p<0.001). Clinically, Grade 2+ pneumonitis was associated with larger median GTV’s of 21.39 cc versus 7.65 cc (p=0.0016), larger median PTV’s of 65.62 cc versus 31.75 cc (p=0.0030), and higher V20 6.62% versus 4.08% (p=0.0408). For patients surviving >1 year, overall local failure rate was 9.4%. Actuarial control rates trended toward statistical significance with time to local failure with VMAT being the most favorable group on the Kaplan-Meier curve (p=0.0733). CONCLUSION: VMAT showed superior conformality compared to the other modalities. Among the modalities examined, HT had higher values for parameters associated with toxicity such as V5 and maximum esophageal dose, but all were within acceptable limits. There was a trend to better local control with VMAT.